2018
DOI: 10.5539/elt.v11n5p104
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influencing Factors of High School English Teacher Professional Learning Community Evaluation in Changchun, China

Abstract: This research shows the development and influencing factors of high school English teachers' evaluation of professional learning community in Changchun, China. Followed Olivier and Hipp & Huffma's research, the teacher professional learning community evaluation questionnaire was developed by the researchers. 422 English teachers in Changchun were invited to participate in the online survey. This study found that the organization characteristics of professional learning communities in this city shared similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Findings from participants' discussion highlighted the misalignment of implementing Western perspectives of PLC practices within their contexts, where Asian cultural values of hierarchy were influential. This trend in findings is highly consistent in cross cultural leadership studies from the wider school literature (Hairon & Dimmock, 2012;Li & Tu, 2018). Principals in this study were cautious in avoiding some dimensions of shared leadership practices found in the PLC survey that may threaten the existing hierarchical practices in their settings.…”
Section: Chapter Summarysupporting
confidence: 80%
“…Findings from participants' discussion highlighted the misalignment of implementing Western perspectives of PLC practices within their contexts, where Asian cultural values of hierarchy were influential. This trend in findings is highly consistent in cross cultural leadership studies from the wider school literature (Hairon & Dimmock, 2012;Li & Tu, 2018). Principals in this study were cautious in avoiding some dimensions of shared leadership practices found in the PLC survey that may threaten the existing hierarchical practices in their settings.…”
Section: Chapter Summarysupporting
confidence: 80%
“…At present, even though the water saving education has various contents and methods, huge differences in their efficiency still exist. In actual practices, some researchers have explored how to improve the influences of education from optimizing medium selection, target audience, teaching ideas and teaching evaluation based on the theory of information communication [6]. For the educated, there is still a gap between their attitude and behavior.…”
Section: Introductionmentioning
confidence: 99%